MicroRNA-32 Suppression: its Effects on Prostate Cancer Cells’ Capability to Proliferate and Migrate - Al-Marzook, Farah A.; Hassan, Duha Maithem; Alghazal, Maha Waleed; Kadheem, Rana Abd Alameer; Jalil, Abduladheem Turki; Saleh, Marwan Mahmood (Drug Research, 2023)
Introduction This paper sought to scrutinize the role of microRNA-32 (miR-32) on the growth and migration as well as on the expression of metastatic genes in PC3 cells of prostate cancer in vitro.Methods Subsequent transfection of cells with miR-32 mimics, miR-32 inhibitor, negative control (NC), cell proliferation using MTT, and apoptosis by ELISA were performed. Furthermore, qRT-PCR was directed to measure the expression levels of matrix metalloproteinase 2 (MMP2) and vascular endothelial growth factors (VEGF) as metastatic and angiogenesis genes in the progression of PC3.Results miR-32 was overexpressed in PC3 cells compared to normal cells (P<0.001). Down-regulation of miR-32 obstructs in vitro proliferation and migration while intensifying the apoptosis rate in PC3 cells. Also, we found that miR-32 negatively modulates the expression of VEGF and MMP2 in PC3 cells.Conclusion These results indicate that the suppression of miR-32 might offer an auxiliary treatment procedure for addressing the invasion, progression, and metastasis in PCa patients by improving cell apoptosis.
Keywords: prostate cancer; miR-32; metastasis; proliferation; migration.